2014
DOI: 10.1002/adsc.201400463
|View full text |Cite
|
Sign up to set email alerts
|

Copper Catalysts for Selective CC Bond Cleavage of β‐O‐4 Lignin Model Compounds

Abstract: The reactivity of homogeneous copper catalysts towards the selective CC bond cleavage of both phenolic and non‐phenolic arylglycerol β‐aryl ether lignin model compounds has been explored. Several copper precursors, nitrogen ligands, and solvents were evaluated in order to optimize the catalyst system. Using the optimized catalyst system, copper(I) trifluoromethanesulfonate [Cu(OTf)]/L/TEMPO (L=2,6‐lutidine, TEMPO=2,2,6,6‐tetramethyl‐piperidin‐1‐yl‐oxyl), aerobic oxidation of the non‐phenolic β‐O‐4 lignin mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 75 publications
0
68
0
1
Order By: Relevance
“…[344] Acoppercatalysed oxidative process on the same model compound, by contrast, led primarily to an a-ketone. [345] These examples again outline the need of acareful choice of model compound and catalytic parameters,a st he modification of as ingle substituent or metal complex can exert aprofound influence on the predominant depolymerisation pathway(s).…”
Section: (Dtbby)][pfmentioning
confidence: 99%
“…[344] Acoppercatalysed oxidative process on the same model compound, by contrast, led primarily to an a-ketone. [345] These examples again outline the need of acareful choice of model compound and catalytic parameters,a st he modification of as ingle substituent or metal complex can exert aprofound influence on the predominant depolymerisation pathway(s).…”
Section: (Dtbby)][pfmentioning
confidence: 99%
“…The CuOTf/TEMPO catalyst 4, consisted of 10 wt% CuOTf, 10 wt% TEMPO and 100 wt% 2,6lutidine in dimethylformamide (DMF), the mixture was then heated at 100 C for 18 h. 26 For catalysts 3, 5 and 6, we used the reported conditions (solvents, temperature and catalyst loading) in order to avoid variability in the catalyst performance, although O 2 pressure in our experiment was lower than that reported for the Co catalyst. Aer 18 h, 400 mL aliquots were removed and analyzed by GPC, q-HSQC and 31 P NMR spectroscopy (see ESI † for details).…”
Section: Procedures For the Catalytic Oxidation Of Organosolv Ligninmentioning
confidence: 99%
“…In previous studies we [22][23][24] and Hanson and co-workers 39 showed that oxovanadium(V) complexes, 1 and 2 ( Fig. 27 In contrast, the Cu catalyst system 4 leads to direct cleavage of the C a -C b bond to give primarily the aldehyde product, presumably through a single-electron transfer pathway 26,32,33 reminiscent of peroxidase enzymes. Subsequent cleavage of the C a -C b bond in the aryl ketone then gives aldehyde and acid products.…”
Section: Introductionmentioning
confidence: 98%
“…Sedai and Baker reported an effective combined catalytic system containing CuCl and TEMPO for the oxidation of 1,2-diphenyl-2-methoxyethanol (model 8, W = OCH 3 , Fig. 8), having β-1 linkage, using O 2 as the oxidant [64]. After 48 h reaction at 100 °C, they achieved more than 80% of β-1 cleavage.…”
Section: Tempo Mediated Oxidative C-c Cleavagementioning
confidence: 99%